Impacts of Diet and Exercise on Maternal Gut Microbiota Are Transferred to Offspring - Bhagavata Srinivasan, Shyam Prakaash; Raipuria, Mukesh; Bahari, Hasnah; Kaakoush, Nadeem O.; Morris, Margaret J. (Frontiers in Endocrinology, 2018)
Background It is well established that maternal exercise during pregnancy improves metabolic outcomes associated with obesity in mothers and offspring, however, its effects on the gut microbiota of both mother and offspring, are unknown. Here, we investigated whether wheel running exercise prior to and during pregnancy and prolonged feeding of an obesogenic diet were associated with changes in the gut microbiomes of Sprague-Dawley rat dams and their offspring. Female rats were fed either chow or obesogenic diet, and half of each diet group were given access to a running wheel 10 days before mating until delivery, while others remained sedentary. 16S rRNA gene amplicon sequencing was used to assess gut microbial communities in dams and their male and female offspring around the time of weaning. Results Statistical analyses at the operational taxonomic unit (OTU) level revealed that maternal obesogenic diet decreased gut microbial alpha diversity and altered abundances of bacterial taxa previously associated with obesity such as Bacteroides and Blautia in dams, and their offspring of both sexes. Distance based linear modelling revealed that the relative abundances of Bacteroides OTUs were associated with adiposity measures in both dams and offspring. We identified no marked effects of maternal exercise on the gut microbiota of obesogenic diet dams or their offspring. In contrast, maternal exercise decreased gut microbial alpha diversity and altered the abundance of 88 microbial taxa in offspring of control dams. Thirty of these taxa were altered in a similar direction in offspring of sedentary obesogenic versus control diet dams. In particular, the relative abundances of Oscillibacter OTUs were decreased in offspring of both exercised control dams and sedentary obesogenic diet dams, and associated with blood glucose concentrations and adiposity measures. Conclusions Our data suggest that maternal exercise prior to and during pregnancy resulted in gut dysbiosis in offspring of control dams. Importantly, alterations in the maternal gut microbiota by obesogenic diet or obesity were transferred to their offspring.